2020
DOI: 10.1016/j.jhepr.2020.100137
|View full text |Cite
|
Sign up to set email alerts
|

Volatomic analysis identifies compounds that can stratify non-alcoholic fatty liver disease

Abstract: Background & aims Analysis of volatile organic compounds (VOCs) in exhaled breath, ‘volatomics’, provides opportunities for non-invasive biomarker discovery and novel mechanistic insights into a variety of diseases. The purpose of this pilot study was to compare breath VOCs in an initial cohort of patients with non-alcoholic fatty liver disease (NAFLD) and healthy controls. Methods Breath samples were collected from 15 participants with Child-Pugh class A NAFLD cirrhosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 45 publications
3
17
0
1
Order By: Relevance
“…In this study, we have significantly expanded on this concept by showing that limonene correlates with established blood metrics of liver function, but not with ALT, a biomarker of liver damage. In agreement with our results, Sinha et al ( 30 ) also mentioned a negative correlation between breath limonene and serum albumin. A difference can be observed with a study by Friedman et al ( 15 ) that showed a correlation between lung air limonene and prothrombin time, but not with serum bilirubin and albumin.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, we have significantly expanded on this concept by showing that limonene correlates with established blood metrics of liver function, but not with ALT, a biomarker of liver damage. In agreement with our results, Sinha et al ( 30 ) also mentioned a negative correlation between breath limonene and serum albumin. A difference can be observed with a study by Friedman et al ( 15 ) that showed a correlation between lung air limonene and prothrombin time, but not with serum bilirubin and albumin.…”
Section: Discussionsupporting
confidence: 94%
“…Our results confirm and expand on previous findings by O'Hara et al ( 17 ) who demonstrated that limonene levels are elevated in subjects with HCC and cirrhosis and a study by Fernandez Del Rio et al ( 14 ) which showed that restoring hepatic function by liver transplant brings breath limonene levels to baseline in the following weeks. Similarly, Sinha et al ( 30 ) found high levels of limonene in the breath of patients with non-alcoholic steatohepatitis (NASH) cirrhosis, compared with those of patients with non-alcoholic fatty liver disease, further supporting our conclusion that cirrhosis is the primary driver for the elevation of breath limonene levels.…”
Section: Discussionsupporting
confidence: 88%
“… 40 Measurement of volatile organic compounds, such as erpinene, dimethyl sulfide, and D-limonene, in breath is another approach that may prove useful in diagnosing and managing some liver diseases. 41 , 42 These approaches have also been termed volatomics or breath biopsy. Although many of these tests do show reasonable correlation with other tests of liver function, they are not indicated for the diagnosis of disease and are of limited value in measuring degrees of fibrosis, steatosis or inflammation.…”
Section: Limitations Of Liver Biopsymentioning
confidence: 99%
“…Therefore, there has been an increasing interest in nutrigenomics, proteomics, and metabolomics to monitor metabolism from a wider perspective. Volatomic analysis of exhaled breath, used mainly for searching noninvasive biomarkers for diseases [ 19 , 20 , 21 ], could be used to characterize volatile organic compounds (VOCs) relating to various diets or specific foods, such as WG cereals. This research could lead to new information on the metabolic effects of WG foods and their association with health effects.…”
Section: Introductionmentioning
confidence: 99%